Targeting KRAS in Lung Cancer Beyond KRAS G12C Inhibitors: The Immune Regulatory Role of KRAS and Novel Therapeutic Strategies - Cucurull, Marc; Notario, Lucia; Sanchez-Cespedes, Montse; Hierro, Cinta; Estival, Anna; Carcereny, Enric; Saigí, Maria (Frontiers in Oncology, 2022)
Approximately 20% of lung adenocarcinomas harbor KRAS mutations, an oncogene that drives tumorigenesis and has the ability to alter the immune system and the tumor immune microenvironment. While KRAS was considered “undruggable” for decades, specific KRAS G12C covalent inhibitors have recently emerged, although their promising results are limited to a subset of patients. Several other drugs targeting KRAS activation and downstream signaling pathways are currently under investigation in early-phase clinical trials. In addition, KRAS mutations can co-exist with other mutations in significant genes in cancer (eg. STK11 and KEAP1) which induces tumor heterogeneity and promotes different responses to therapies. This review describes the molecular characterization of KRAS mutant lung cancers from a biologic perspective to its clinical implications. We aim to summarize the tumor heterogeneity of KRAS mutant lung cancers and its immune-regulatory role, to report the efficacy achieved with current immunotherapies, and to overview the therapeutic approaches targeting KRAS mutations besides KRAS G12C inhibitors.